3-(4-Bromophenylsulfinyl)-5-cyclohexyl-2-methyl-1-benzofuran - Choi, Hong Dae (International Union of Crystallography, 2011)
In the title compound, C(21)H(21)BrO(2)S, the cyclohexyl ring adopts a chair conformation. The 4-bromophenyl ring makes a dihedral angle of 81.62 (6)° with the mean plane of the benzofuran fragment. In the crystal, molecules are linked by weak C—H⋯O and C—H⋯π interactions. The crystal structure also exhibits a slipped π–π interaction between the furan rings of neighbouring molecules [centroid–centroid distances = 3.540 (3) Å, interplanar distance = 3.481 (3) Å and slippage = 0.644 (3) Å].